2014
DOI: 10.18632/oncotarget.3243
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine, an antidepressant, suppresses glioblastoma by evoking AMPAR-mediated calcium-dependent apoptosis

Abstract: The efficacy of glioblastoma chemotherapy is not satisfactory; therefore, a new medication is expected to improve outcomes. As much evidence shows that antidepressants decrease cancer incidence and improve patients' quality of life, we therefore attempted to explore the potential for fluoxetine to be used to treat GBM and its possible underlying mechanism. The expression level of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) was determined using immunohistochemical staining and PCR anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
81
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 51 publications
2
81
0
Order By: Relevance
“…In addition, the dosage of fluoxetine as a chemosensitizer is kept under the range of 5-20 µM, where this agent itself does not affect cell viability (15). In the present study, fluoxetine at 10 µM did not induce apoptosis, whereas higher concentrations of fluoxetine (>25 µM) could suppress glioblastoma cells by calcium-dependent apoptosis (31). Alternatively, the addition of fluoxetine lessened the IFN-α-induced apoptosis but switched to cause G1 arrest, and maintained the IFN-α-mediated reduction in G2/M phase (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…In addition, the dosage of fluoxetine as a chemosensitizer is kept under the range of 5-20 µM, where this agent itself does not affect cell viability (15). In the present study, fluoxetine at 10 µM did not induce apoptosis, whereas higher concentrations of fluoxetine (>25 µM) could suppress glioblastoma cells by calcium-dependent apoptosis (31). Alternatively, the addition of fluoxetine lessened the IFN-α-induced apoptosis but switched to cause G1 arrest, and maintained the IFN-α-mediated reduction in G2/M phase (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…Growing evidence supports the contribution of altered Ca 2+ signaling to tumor progression and metastasis, suggesting that agents targeting calcium influx and calcium influx-driven downstream signaling may hopefully offer alternative approaches for cancer therapy [17,18]. Several calcium channels blockers have been investigated in clinical trials [1921]; however, their efficacy has not been satisfactory for unclear reasons.…”
Section: Discussionmentioning
confidence: 99%
“…57 It is also possible that the increased cell death in mice receiving fluoxetine (Figure 3A) played a role in the initial poorer performance. Although most studies have indicated that SSRIs tend to potentiate cell survival, a few have demonstrated fluoxetine-induced growth factor reduction 58 as well as SSRI-induced apoptosis, especially of diseased cells, 5962 perhaps by potentiation of the immune system. 63 Nevertheless, despite increased cell death, animals receiving fluoxetine eventually outperformed animals receiving saline.…”
Section: Discussionmentioning
confidence: 99%